The Improving Effects of Humic Acid and Biochar on Yield Components of Barley under Drought Stress - Hussein Ali, Almayyahi, Ahmad; ali, soleymani (Journal of Science in Medicine and Life, 2025)
In order to evaluate the improving effects of humic acid and biochar on yield components of barley (hordeum vulgar L.) under drought stress, a greenhouse study was carried out (2022-23) in Baquba, Diyala Province, Iraq (33˚ 74̍ north and 44˚ 64̍ east with a hot desert climate, average temperature of 22.8 ˚C, 186 mm of precipitation and 2200m altitude) (IBA 99 cultivar). The study was done as factorial experiment in a completely randomized design with three replications. The studied factors were drought stress at three levels (irrigation after draining 33%, 66% and 100% of field capacity) and fertilizer (biochar and humic acid). Measured traits were the number of ears, the number of grains per ear, weight of 1000 grains, grain yield and harvest index. Humic acid consumption plus stress 33%had the highest number of ear and grain yield. Biochar was not very successful in repairing the negative effects of drought. Overall, at all levels of drought stress, humic acid was better than biochar and under the same conditions as the present study, it seems reasonable to use humic acid to eliminate the adverse effects of drought stress and increase the yield without causing environmental problems.